2020
DOI: 10.1101/2020.06.23.20137596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelets can contain SARS-CoV-2 RNA and are hyperactivated in COVID-19

Abstract: Rationale: In addition to the overwhelming lung inflammation that prevails in COVID-19, hypercoagulation and thrombosis contribute to the lethality of subjects infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Platelets are chiefly implicated in thrombosis. Moreover, they can interact with viruses and are an important source of inflammatory mediators. While a lower platelet count is associated with severity and mortality, little is known about platelet function during COVID-19. Object… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 69 publications
5
58
0
Order By: Relevance
“…Actually, the COVID-19 virus can induce ACE2 internalization and subsequent degradation, evidenced by our study of SARS-CoV-2-induced ACE2 degradation in platelets (Additional file 1: Online Figure 5) and the other studies on SARS-CoV-2-induced ACE2 degradation [30]. Moreover, a recent study indicated that SARS-CoV-2 infection could downregulate ACE2 at the mRNA level and this effect requires action directly on the ACE2 promoter [71]. In consistent with the identification of platelet ACE2 in our results, Zaid et al also found that ACE2 mRNA was presented in platelets from both healthy people and COVID-19 patients [72].…”
Section: Discussionmentioning
confidence: 57%
“…Actually, the COVID-19 virus can induce ACE2 internalization and subsequent degradation, evidenced by our study of SARS-CoV-2-induced ACE2 degradation in platelets (Additional file 1: Online Figure 5) and the other studies on SARS-CoV-2-induced ACE2 degradation [30]. Moreover, a recent study indicated that SARS-CoV-2 infection could downregulate ACE2 at the mRNA level and this effect requires action directly on the ACE2 promoter [71]. In consistent with the identification of platelet ACE2 in our results, Zaid et al also found that ACE2 mRNA was presented in platelets from both healthy people and COVID-19 patients [72].…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, this hypothesis is supported by pre-publication evidence reporting the presence of SARS-CoV-2 RNA in platelets of COVID-19 patients, which were shown to be hyperactivated and aggregated at a lower threshold of in vitro thrombin stimulation (125). Platelets from COVID-19 degranulate, which correlates with reduced platelet factor 4 and serotonin levels, and release extracellular vesicles to participate in coagulation (125). Consequently, platelet reprogramming could facilitate the transmission of SARS-CoV-2 and promote thrombo-inflammation.…”
Section: Coagulation Cascades and The Mechanisms Of Thrombosis In Covmentioning
confidence: 74%
“…Platelets from COVID-19 patients induces ex vivo expression of tissue factor (TF) in monocytes (124), indicating a likely reprogramming event during SARS-CoV-2 infection. Indeed, this hypothesis is supported by pre-publication evidence reporting the presence of SARS-CoV-2 RNA in platelets of COVID-19 patients, which were shown to be hyperactivated and aggregated at a lower threshold of in vitro thrombin stimulation (125). Platelets from COVID-19 degranulate, which correlates with reduced platelet factor 4 and serotonin levels, and release extracellular vesicles to participate in coagulation (125).…”
Section: Coagulation Cascades and The Mechanisms Of Thrombosis In Covmentioning
confidence: 90%
“…Recently, several independent studies have demonstrated that platelets are activated in COVID‐19 patients 9‐14 . Platelets from COVID‐19 patients are hyperreactive in comparison to healthy donors when activated with traditional platelet agonists such as adenosine diphospate, collagen, and thrombin.…”
Section: Platelet Activation and Hyperactivty In Covid‐19mentioning
confidence: 99%